The sexual health assessment of practices and experiences (SHAPE) questionnaire: Adaptation Process and Results of the Data Collected during the Pre-Test in Portugal - Ana Luísa Patrão; Maria Yolanda Makuch; Vilma Zotareli; Pedro Nobre (O Mundo da Saúde)
The Sexual Health Assessment of Practices and Experiences (SHAPE) Questionnaire developed by the World Health Organization is being implemented and tested for the first time worldwide in Portugal. The objective of this study is to describe the adaptation process and the results of the data collected during the pre-test. Pretesting was conducted with a sample of 40 individuals (60% women; mean age 53.9 years). Half of the questionnaires were answered online and half by telephone interview. The online response rate was 76.9% and telephone was 11.3%. Of the telephone interviews, the principal reason for refusing to participate was that the subject was so personal. SHAPE was well accepted, with 95% of respondents answering the questions on pregnancy, 97.5% answering those on sexually transmitted infections and 97.5% answering the questions on non-consensual sexual experiences. The existence of an instrument dealing with the behavioral and psychosocial components of sexual and reproductive health, adapted for use in the Portuguese population while also being applicable on a global level, will permit comprehensive and comparative studies to be developed that will benefit health promotion in general and sexual and reproductive health in particular.